Integrating Treatment for Autism: Etiology and Life Cycle - R.M. Tsipan; C.I. Parenteau; R.L. Hendren (Moscow State University of Psychology and Education, 2020)
Autism Spectrum Disorder (ASD) is linked to a multitude of genes, epigenetics, and environmental factors, which contribute to the complexities of treating ASD. A large body of literature suggests benefits from perinatal, early, and later intervention. It is common for physicians to struggle with making a diagnosis of ASD, but once it is made, parents who have been taught effective strategies can be impactful in their child's positive development. Neuroimaging studies of children, adolescents and young adults with ASD suggest that their brain structures change over time and are also capable of being shaped through appropriate interventions. Interventions are also being adapted for adults with ASD to better address their needs, such as employment training programs. We review the wide array of risk factors and interventions to mitigate the challenges individuals with ASD face in their daily lives.